METHODOLOGY FOR DEVELOPING LANGUAGE SKILLS OF FUTURE GERMAN LANGUAGE TEACHERS - Jumayeva Gulkhan Amrullayevna (Bright Mind Publishing, 2025)
Today, under the influence of globalization processes, the study and teaching of foreign languages is gaining importance. In particular, since German is accepted as an official language in many European countries, the task of teaching this language to Uzbek youth is of great importance. Improving the methodology for developing language skills of future German teachers plays an important role in improving the professional qualifications of teachers. This article provides information on the main factors and approaches necessary for improving the methodology for developing language skills of German teachers.
Keywords: Future German teachers, language, methodology, knowledge, skills, modern pedagogical technologies, group work, discussion, role-playing games, interactive methods.